Challenges encountered by newly arrived Thai students when learning Indonesian as a foreign language - Fendy Yogha Pratama; Andayani Andayani; Retno Winarni; Muhammad Rohmadi (Institute of Advanced Engineering and Science, 2024)
This study aimed to determine the challenges faced by Thai international students when they first came to Indonesia to study Indonesian as a foreign language. There were nine Thai students studying in six different cities in Indonesia were recruited as participants. The thematic analysis revealed two major themes: academic challenges and technological issues. Both made it difficult for Thai students to master the Indonesian language effectively. The condition potentially hinders their academic success when studying in Indonesia. However, the researchers found that despite the language barrier, Thai students still tried to speak Indonesian with Indonesian students and residents. It indicates that Thai students in this study were highly determined, friendly, and open to new cultures. Furthermore, the researchers advise teachers and program organizers to pay attention to these challenges to maximize the learning output.